The perceptions of host-city residents of the impact of mega-events and their support: the EXPO 2020 in Dubai. Issue 3 (2nd September 2021) - Al Hallaq, Ahmad; Ninov, Ivan; Dutt, Christopher S.
ABSTRACT: Events tourism has been growing rapidly and has become one of the most common ways of attracting tourists to developing destinations. Hosting mega-events has become a means to achieve rapid development in a destination. Host-city residents are the first to feel the impact of hosting such events and are considered as key stakeholders. Results from a survey distributed in Dubai revealed that residents supported the upcoming EXPO 2020 event, with little concern for the potential associated costs – a result contradicting a lot of literature. The results provide guidance for policy makers regarding host-city residents' perceptions on hosting events.